Eumelanin and pheomelanin pigmentation in mollusc shells may be less common than expected: insights from mass spectrometry - Affenzeller, Susanne (Front Zool, 2019)
BACKGROUND: The geometric patterns that adorn the shells of many phylogenetically disparate molluscan species are comprised of pigments that span the visible spectrum. Although early chemical studies implicated melanin as a commonly employed pigment, surprisingly little evidence generated with more recent and sensitive techniques exists to support these observations. RESULTS: Here we present the first mass spectrometric investigations for the presence of eumelanin and pheomelanin in 13 different molluscan species from three conchiferan classes: Bivalvia, Cephalopoda and Gastropoda. In the bivalve Mytilus edulis we demonstrate that eumelanin mainly occurs in the outermost, non-mineralised and highly pigmented layer of the shell (often referred to as the periostracum). We also identified eumelanin in the shells of the cephalopod Nautilus pompilius and the marine gastropods Clanculus pharaonius and Steromphala adriatica. In the terrestrial gastropod Cepaea nemoralis we verify the presence of pheomelanin in a mollusc shell for the first time. Surprisingly, in a large number of brown/black coloured shells we did not find any evidence for either type of melanin. CONCLUSIONS: We recommend methods such as high-performance liquid chromatography with mass spectrometric detection for the analysis of complex biological samples to avoid potential false-positive identification of melanin. Our results imply that many molluscan species employ as yet unidentified pigments to pattern their shells. This has implications for our understanding of how molluscs evolved the ability to pigment and pattern their shells, and for the identification of the molecular mechanisms that regulate these processes.